Comparison of Contrast Sensitivity and Through Focus in Small-Aperture Inlay, Accommodating Intraocular Lens, or Multifocal Intraocular Lens Subjects - Vilupuru, Srividhya; Lin, Ling; Pepose, Jay S. (American journal of ophthalmology, 2015)
To compare monocular and binocular mesopic contrast sensitivity and through focus following monocular implantation with KAMRA small-aperture inlay (AcuFocus, Irvine, California, USA) vs binocular implantation with an accommodating or multifocal intraocular lens (IOL) implant. Three-treatment randomized clinical trial of presbyopia-correcting IOLs with comparison to results from a previous nonrandomized multicenter clinical trial on the KAMRA corneal inlay. Study population of 507 subjects with KAMRA inlays; predetermined subgroups included 327 subjects that underwent contrast sensitivity testing and another 114 subjects for defocus curve testing, along with 78 subjects randomized between bilateral Crystalens Advanced Optics (AO) (Bausch + Lomb Surgical, Aliso Viejo, California, USA), AcrySof IQ ReSTOR +3.0 D (Alcon Laboratories, Fort Worth, Texas, USA), or Tecnis +4D Multifocal (MF) (Abbott Medical Optics, Santa Ana, California, USA) IOL. KAMRA inlay subjects demonstrated improved intermediate and near vision with minimal to no change to distance vision, better contrast sensitivity in the inlay eye when compared to the multifocals, and better binocular contrast sensitivity when compared to all 3 intraocular lenses. Crystalens AO was superior in uncorrected intermediate vision compared to the KAMRA inlay, but not in distance-corrected intermediate, and was worse in near vision. The multifocals were superior in near vision at their respective optimum near focus points, but worse in intermediate vision compared to both KAMRA inlay and Crystalens AO. The demonstrated performance of these devices should be considered, along with subjects' visual demands and expectations, degree of crystalline lens dysfunction, and other ocular characteristics, in guiding the selection of small-aperture corneal inlay or specific intraocular lens in the correction of presbyopia.